Redefine Our Nationalism? Critical Reflection on Indonesian Nationalism as a "Joint Project": Case Study of Post-1998 Racial Communal Conflict - Donny Maulana; Hariyono, Hariyono; Utami, Indah Wahyu Puji (Yupa: Historical Studies Journal, 2024)
The discourse on Indonesian Nationalism will never end. As the basis of the state, nationalism needs to continue to be reflected to remain relevant to current developments. The phenomenon of narrowing the meaning of Indonesian Nationalism and stagnation in the mainstream narrative which leads to the fossilisation of meaning is also an important and urgent topic to study. The big question is whether Indonesian Nationalism is still on rails and corridors that are relevant to the current condition of the nation. This article will specifically dissect in a deconstructive manner the paradigm of Indonesian Nationalism as a "joint project" as a form of response to stagnation and narrow mainstream narratives about nationalism. This paper also analyzes it in a historical framework, specifically taking a case study of racial communal conflict after the 1998 Reformation using the analytical knife of Benedict Anderson's Imagined Communities. There are three sub-discussions which will explain the background conditions and challenges of Indonesian Nationalism, the deconstruction of the paradigm of Indonesian Nationalism and how nationalism should be addressed as a "joint project" of a nation.